Current Advances and Future Directions in Targeting Histone Demethylases for Cancer Therapy - June-Ha Shin; Hye-Been Yoo; Jae‐Seok Roe (2025)
Epigenetic regulators, known as "writers," erasers," and "readers," are essential for controlling gene expression by adding, removing, or recognizing posttranslational modifications to histone tails, respectively. These regulators significantly affect genes involved in cancer initiation and maintenance. Recently, several clinical strategies targeting these epigenetic enzymes have emerged and some trials have demonstrated promising results for cancer treatment. Histone lysine demethylases (KDMs) yield distinct transcriptional outcomes that depend on the position of the methylated lysine and the specific genotype or lineage of the cancer cells. Due to their diverse roles in transcription, KDMs offer valuable opportunities for precision oncology, allowing treatments to be tailored to meet individual patient needs. This review emphasizes our current understanding of the functional relationship between KDMs and cancer as well as the development and application of small-molecule compounds that target KDMs.